A Comparative Study of Outcomes of Treatments for Radiculopathies Arising out of Single Level Disc Prolapse of Lumbar Spine Treated with Epidural Steroid Injections Versus Conservative Management (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: epidural steroid injection; single level disc prolapse; lumbar degenerative disc disease